Oral mucosa lesions as atypical manifestation of adult-onset Still´s disease - María Lorena Brance; Eldo Luis Neffen (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Adult-onset Still's disease is a systemic inflammatory disorder of unknown etiology, characterized by skin rash, spiking fever, arthralgias or arthritis, and leukocytosis. The typical skin rash is evanescent, salmon-pink, nonpruritic and maculopapular, predominantly on the extremities. It is considered one of the major Yamaguchi's criteria in adult-onset Still's disease. However, atypical skin lesions are also described. Here, a 61-year-old woman with sore throat, spiking fever, polyarthritis and evanescent salmon-pink nonpruritic maculopapular skin rash on the extremities was diagnosed with adult-onset Still's disease. In addition, atypical brown macules on oral mucosa, localized on the inner lips and tongue were also observed. Biopsy revealed a neutrophilic infiltrate. Despite treatment and improvement of the adult-onset Still's disease, the atypical oral mucosal lesions persisted.